Dual-Phase Dual-Energy CT in Patients Treated with Erlotinib for Advanced Non-Small Cell Lung Cancer: Possible Benefits of Iodine Quantification in Response Assessment - Baxa, Jan; Matouskova, Tana; Krakorova, Gabriela; Schmidt, Bernhard; Flohr, Thomas; Sedlmair, Martin; Bejcek, Jiri; Ferda, Jiri (European radiology, 2016)
OBJECTIVES: To investigate the relationship of dual-phase dual-energy CT (DE-CT) and tumour size in the evaluation of the response to anti-EGFR therapy in patients with advanced non-small cell lung cancer (NSCLC). METHODS: Dual-phase DE-CT was performed in 31 patients with NSCLC before the onset of anti-EGFR (erlotinib) therapy and as follow-up (mean 8 weeks). Iodine uptake (IU; mg/mL) was quantified using prototype software in arterial and venous phases; arterial enhancement fraction (AEF) was calculated. The change of IU before and after therapy onset was compared with anatomical evaluation in maximal transverse diameter and volume (responders vs. non-responders). RESULTS: A significant decrease of IU in venous phase was proved in responders according to all anatomical parameters (p=0.002-0.016). In groups of non-responders, a significant change of IU was not proved with variable trends of development. The most significant change was observed using the anatomical parameter of volume (cut-off 73 %). A significant difference of percentage change in AEF was proved between responding and non-responders (p=0.019-0.043). CONCLUSION: Dual-phase DE-CT with iodine uptake quantification is a feasible method with potential benefit in advanced assessment of anti-EGFR therapy response. We demonstrated a decrease in vascularization in the responding primary tumours and non-significant variable development of vascularization in non-responding tumours. KEY POINTS: • Dual-phase DE-CT is feasible for vascularization assessment of NSCLC with anti-EGFR therapy. • There was a significant decrease of iodine uptake in responding tumours. • There was a non-significant and variable development in non-responding tumours. • There was significant difference of AEF percentage change between responders and non-responders.
Keywords: Erlotinib Hydrochloride; Female; Lymphatic Metastasis; lymfatické metastázy; nemalobuněčný karcinom plic; ženské pohlaví; Tomography, X-Ray Computed; nádory plic; Iodine; Reproducibility of Results; lymfatické uzliny; lidé; Antineoplastic Agents; staging nádorů; protinádorové látky; Humans; reprodukovatelnost výsledků; Male; Aged; Carcinoma, Non-Small-Cell Lung; erlotinib; Lymph Nodes; Lung Neoplasms; jod; lidé středního věku; pozitronová emisní tomografie; senioři; mužské pohlaví; Middle Aged; Neoplasm Staging; Positron-Emission Tomography; počítačová rentgenová tomografie